Human Adipose Tissue-Derived Mesenchymal Stem Cells Attenuate Atopic Dermatitis by Regulating the Expression of MIP-2, miR-122a-SOCS1 Axis, and Th1/Th2 Responses - Kim, Misun; Lee, Sung-Hoon; Kim, Youngmi; Kwon, Yoojung; Park, Yeongseo; Lee, Hong-Ki; Jung, Hyun Suk; Jeoung, Dooil (Frontiers in Pharmacology, 2018)
The objective of this study was to investigate the effect of human adipose tissue-derived mesenchymal stem cells (AdMSCs) on atopic dermatitis (AD) in BALB/c mouse model. AdMSCs attenuated clinical symptoms associated with AD, decreased numbers of degranulated mast cells, IgE level, amount of histamine released, and prostaglandin E2 level. AD increased expression levels of cytokines/chemokines, such as IL-5, MIP-1ß, MIP-2, CCL5, and IL-17, in BALB/c mouse. AdMSCs decreased expression levels of these cytokines in mouse model of AD. In vivo down-regulation of MIP-2 attenuated clinical symptoms associated with AD. AD increased expression levels of hallmarks of allergic inflammation, induced interactions of FcεRIβ with HDAC3 and Lyn, increased ß-hexosaminidase activity, serum IgE level, and the amount of histamine released in MIP-2-dependent manner. Down-regulation of MIP-2 increased several miRNAs including miR-122a-5p. Mouse miR-122a-5p mimic inhibited AD while SOCS1, a predicted downstream target of miR-122a-5p, was required for AD. The down-regulation of SOCS1 decreased expression levels of MIP-2 and CXCL13 in mouse model of AD. Down-regulation of CXCL13 attenuated atopic dermatitis and allergic inflammation such as passive cutaneous anaphylaxis. The role of T cell transcription factors in AD was also investigated. AD increased expression levels of T-bet and GATA-3 [transcription factor of T-helper 1(Th1) and T-helper 2 (Th2), respectively], but decreased expression of Foxp3, a transcription factor of regulatory T (Treg) cells, in SOCS1-dependent manner. MiR-122a-5p mimic also prevented AD from regulating the expression of T-bet, GATA-3 and Foxp3. AD increased expression of CD163, a marker of M2 macrophages, but decreased expression of iNOS, a marker of M1 macrophages. SOCS1 and miR-122a-5p mimic regulated expression of CD163 and iNOS in mouse model of AD. Experiments employing conditioned medium showed interactions between mast cells and macrophages in AD. The conditioned medium of AdMSCs, but not conditioned medium of human dermal fibroblasts, negatively inhibited features of allergic inflammation. In summary, we investigated anti-atopic effects of AdMSCs, identified targets of AdMSCs, and determined underlying mechanism for the anti-atopic effects of AdMSCs.